Wind power development in the Belt and Road area of Xinjiang, China: Problems and solutions. (June 2020) - Wu, Geng; Wang, Haojing; Wu, Qingguo
Abstract: Following the proposal of the "Belt and Road" strategy, Xinjiang has gradually become a critical wind power base and energy transmission channel in China. At present, however, much of Xinjiang's potential wind power is being curtailed. Owing to Xinjiang's strategic position, this issue may negatively impact wind power development in Xinjiang and China's overall energy strategy, and it is thus necessary to identify the causes of and solutions to wind power curtailment in Xinjiang. This study analyzes the problem of wind power development in Xinjiang, and proposes both technical and market policy measures. The research results show that establishing a regional power spot market and improving power system flexibility are the fundamental ways to solve the problem of wind power curtailment in Xinjiang. Highlights: The status quo of wind development and accommodation in Xinjiang are presented. The technology and mechanism of wind power accommodation in Xinjiang are analyzed in detail. The corresponding solutions to solve the problem of wind power accommodation in Xinjiang are proposed.